PENERAPAN STRATEGI PEMBELAJARAN EVERYONE IS A TEACHER HERE UNTUK MENINGKATKAN MOTIVASI BELAJAR IPS KELAS IV SD NEGERI I TEMPURSARI KLATEN TAHUN 2013/ 2014 - Amalia, Nur; Setiyani, Diah (Profesi Pendidikan Dasar, 2014)
This study aims to elevate motivation to learn social studies of fourth grade students of SDNegeri I Tempursari Klaten, academic year 2013/2014. This research is a classroom actionresearch. The subjects in this study were the teacher and fourth grade students. The datacollection techniques used are observation, testing, and documentation. The data analysistechnique used is interactive qualitative analysis through three stages, i.e. data reduction,data exposure and conclusion construction. The results showed that there is an increase instudents’ motivation at the second cycle that reaches 80 % of the initial condition, 33.33 %. It is evident that the number of students who are 1) enthusiastic students in participatinglearning social studies reached 80% of total students; 2) active in the learning process reached80%; 3) working diligently in the testing was 86.67%; 4) able to create a conducive learningenvironment reached 80%; 5) able to work on the problems well reached 86.67 %. Therefore,it can be concluded from this study that the learning strategy, everyone is a teacherhere, can increase the students’ motivation in learning social study.